Intercarrier interference self-cancellation scheme for OFDM mobile communication systems. - Yuping Zhao
For orthogonal frequency-division multiplexing (OFDM) communication systems, the frequency offsets in mobile radio channels distort the orthogonality between subcarriers resulting in intercarrier interference (ICI). This paper studies an efficient ICI cancellation method termed ICI self-cancellation scheme. The scheme works in two very simple steps. At the transmitter side, one data symbol is modulated onto a group of adjacent subcarriers with a group of weighting coefficients. The weighting coefficients are designed so that the ICI caused by the channel frequency errors can be minimized. At the receiver side, by linearly combining the received signals on these subcarriers with proposed coefficients, the residual ICI contained in the received signals can then be further reduced. The carrier-to-interference power ratio (CIR) can be increased by 15 and 30 dB when the group size is two or three, respectively, for a channel with a constant frequency offset. Although the redundant modulation causes a reduction in bandwidth efficiency, it can be compensated, for example, by using larger signal alphabet sizes. Simulations show that OFDM systems using the proposed ICI self-cancellation scheme perform much better than standard systems while having the same bandwidth efficiency in multipath mobile radio channels with large Doppler frequencies
Keywords: Doppler frequencies; ICI self-cancellation.; OFDM mobile communication systems; Bandwidth efficiency; Carrier-to-interference power ratio; Channel frequency errors; Coefficients; Frequency offsets; Group size; Intercarrier interference; Intercarrier interference self-cancellation.; Mobile radio channels; Multipath mobile radio channels; Orthogonal frequency-division multiplexing; Receiver; Redundant modulation; Signal alphabet size; Simulations; Subcarriers; Transmitter; Weighting coefficients